Formulasi Sereal Berbasis Tepung Ubi Ungu, Tepung Tempe, dan Telur Puyuh sebagai Makanan Tambahan Alternatif untuk Balita Gizi Kurang - Khoerunnisa, Awalia; Permatasari, Tria Astika Endah (Poltekkes Kemenkes Semarang, 2023)
Background: The government's effort to overcome toddlers with malnutrition is by providing additional food through local food diversification. One form of alternative food that can be made is in the form of cereals made from local food, purple sweet potato flour, tempeh flour, and quail eggs; Objective: Knowing the formula, quality and hedonicity, and the nutritional content of cereals based on purple sweet potato flour, tempeh flour, and quail eggs as alternative food additives for undernourished toddlers;Method: The study used an experimental design. Consisting of three types of treatment, with a ratio of purple yam flou and tempeh flour, namely 50%: 50% (F1), 60%: 40% (F2), and 80%: 20% (F3). The best cereal formula was obtained through a hedonic test with semi-trained panelists, nutritional content test using proximate analysis;Results: The cereal formula chosen was F3 with 494 kcal of energy, 7.06 grams of protein, 23.78 grams of fat, 62.96 grams of carbohydrates, 4.25% water content, and 1.96 grams of ash content. 51 of 2016 and SNI 01-7111.2-2005 regarding nutritional supplementation product standards, the protein and fat content of cereals has not met the requirements while the energy, carbohydrate, water, and ash content have met the requirements; Conclusion: The cereal formulation chosen was F3 with a ratio of 80% purple sweet potato flour and 20% tempeh flour. It is necessary to improve the cereal formula so that it meets the quality requirements for complementary foods for toddlers.